Equivalence of the effective Hamiltonian approach and the Siegert boundary condition for resonant states. Issue 2 (6th June 2012) - Hatano, N.; Bird, J.; Kaiser, R.; Rotter, I.; Wunner, G.
Abstract Two theoretical methods of finding resonant states in open quantum systems, namely the approach of the Siegert boundary condition and the Feshbach formalism, are reviewed and shown to be algebraically equivalent to each other for a simple model of the T‐type quantum dot. It is stressed that the seemingly Hermitian Hamiltonian of an open quantum system is implicitly non‐Hermitian outside the Hilbert space. The two theoretical approaches extract an explicitly non‐Hermitian effective Hamiltonian in a contracted space out of the seemingly Hermitian (but implicitly non‐Hermitian) full Hamiltonian in the infinite‐dimensional state space of an open quantum system.